Acid hydroxide, fluorescent light emitter comprising the same, and method for producing the same

JP2025001635APending Publication Date: 2025-01-08KANAGAWA UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024063989
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-20
Filing Date
2024-04-11
Publication Date
2025-01-08

AI Technical Summary

Benefits of technology

【0024】 本発明によれば、より高温域でも水の脱離を抑制できる新しい酸水酸化物、及びレアメタルフリーな新しい蛍光体が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025001635000001_ABST
    Figure 2025001635000001_ABST
Patent Text Reader

Abstract

To provide a new acid hydroxide capable of suppressing desorption of water even in a higher temperature range.SOLUTION: According to an acid hydroxide represented by general formula (1) and having a hexagonal structure, desorption of water is suppressed even in a higher temperature range of 600 to 750°C and has a high thermal stability. Such an acid hydroxide is obtained by heating a mixture containing, for example, a compound serving as an Sr source or a Ba source and a compound serving as a Ga source, or a precursor oxide obtained by calcining the same at 300°C or higher in an atmosphere containing 50 vol.% or more water vapor. In general formula (1), A is Sr or Ba, Z is H or D, x is (6.5-0.5y), and y is 0.7 or more and 1.3 or less. The acid hydroxide is also useful as a fluorescent light emitter. A2Ga3Ox(OZ)y (1)SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an oxyhydroxide, a fluorescent material comprising the same, and a method for producing the same. [Background technology]

[0002] Oxyhydroxides are a type of complex anion compound that contains multiple anions in the same compound. 2- ) and hydroxide ion (OH - ) coexist. Compared to simple oxides, mixed anion compounds have unique crystal structures and coordination environments, and are therefore expected to be used in catalysts, catalyst supports, ion conductors, electrode catalysts, and other applications, taking advantage of properties that oxides do not have.

[0003] Incidentally, various materials such as catalysts, catalyst supports, ion conductors, and electrode catalysts are sometimes used in the medium temperature range (400 to 600°C) or high temperature range (600 to 800°C) depending on their applications. However, in the case of oxyhydroxides, the water molecules contained in the crystal lattice can usually only stably exist up to about 300°C, and water is released in the medium temperature range, so that oxide ions (O 2- ) and hydroxide ion (OH - ) cannot maintain the specific crystal structure of the oxyhydroxide in which it coexists. This significantly limits the applications of the oxyhydroxide having the above-mentioned unique properties.

[0004] As such a material, for example, Non-Patent Document 1 describes a tetragonal oxyhydroxide Ba2In2O5(H2O) x However, it has been reported that water is released from the material at temperatures above 300°C, and the oxyhydroxide crystal structure cannot be maintained at medium temperatures. x is a material that has proton conductivity at low temperatures below 300°C, but in a dry atmosphere above approximately 300°C, it is said that the crystal structure cannot be maintained due to desorption of water, and the proton conductivity is lost.

[0005] Under these circumstances, the present inventors have discovered that Ba2In2O4(OH)2 oxyhydroxide, which has a specific crystal structure, has high thermal stability (see Patent Document 1). This oxyhydroxide hardly loses mass due to water desorption up to a medium temperature range of about 600°C, and it can be said that it offers a wider range of applications than conventional oxyhydroxides.

[0006] Incidentally, in modern society, elements such as LEDs have long been used as light sources for lighting, projectors, etc., instead of conventional incandescent lamps. Some of these elements use light emission generated by irradiating a phosphor made of an inorganic substance with light of a specific wavelength, and the phosphor used therein generally uses a rare earth compound for the purpose of obtaining high-intensity light emission of a desired wavelength (see, for example, Patent Document 2, etc.). However, rare earth elements and other so-called rare metals are materials for which resource depletion and geopolitical influences must always be taken into consideration, since their reserves are small and the countries where they are produced are limited. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2020-70203 A [Patent Document 2] JP 2019-6967 A [Non-patent literature]

[0008] [Non-Patent Document 1] J. Bielecki, SF Parker, L. Mazzei, L. Borjessona, M. Karlsson, J. Mater. Chem. A 4, 1225 (2016). Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention has been made in consideration of the above circumstances, and aims to provide a new oxyhydroxide that can suppress water desorption even at higher temperatures, and to provide a new rare metal-free phosphor. [Means for solving the problem]

[0010] As a result of intensive research conducted by the present inventors to solve the above problems, they have found that a mixture containing a compound serving as a Sr source or a Ba source and a compound serving as a Ga source, or a precursor oxide obtained by calcining the mixture, is subjected to an oxyhydroxide reaction in which high-concentration water vapor is allowed to act under high-temperature conditions to obtain Sr-Ga oxyhydroxide or Ba-Ga oxyhydroxide, and that the oxyhydroxide has high thermal stability that inhibits water desorption even at high temperatures of about 600 to 750° C., and that, unexpectedly, the oxyhydroxide exhibits fluorescent emission. The present invention has been made based on these findings and provides the following:

[0011] (1) The present invention relates to an oxyhydroxide having a hexagonal crystal structure represented by the following general formula (1): A2Ga3O x (OZ) y (1) (In the general formula (1), A is Sr or Ba, Z is H (hydrogen atom) or D (deuterium atom), x is (6.5-0.5y), and y is 0.7 or more and 1.3 or less.)

[0012] (2) The present invention also relates to an oxyhydroxide according to item (1), which, when heated from 25°C to 900°C at a heating rate of 10°C / min in nitrogen, experiences a mass loss due to water desorption at a temperature between 600°C and 900°C of 1 mass% or more relative to the mass before heating in thermogravimetric analysis.

[0013] (3) The present invention also relates to an oxyhydroxide according to item (1) or (2), which, in a thermogravimetric analysis in nitrogen, loses less than 1% by mass when heated from 25° C. to 600° C. at a heating rate of 10° C. / min relative to the mass before heating.

[0014] (4) The present invention also provides a method for producing a crystal having a diffraction pattern measured by X-ray diffraction measurement using CuKα radiation as an X-ray source, the diffraction peak of which is at least 2θ=9.36°~9.80°, 12.82°~13.56°, 18.29°~19.61°, 25.89°~28.37°, 27.61°~30.39° and 29.90°~33.22° The oxyhydroxide according to any one of items (1) to (3) has a crystal structure appearing in each of the ranges.

[0015] (5) The present invention also relates to an oxyhydroxide according to any one of (1) to (4), which is represented by the chemical formula Sr2Ga3O6(OH), Sr2Ga3O6(OD), Ba2Ga3O6(OH) or Ba2Ga3O6(OD).

[0016] (6) The present invention also relates to a fluorescent material comprising the oxyhydroxide according to any one of (1) to (5).

[0017] (7) The present invention also relates to a method for producing an oxyhydroxide represented by the following general formula (1), comprising a step of heating a mixture containing a compound serving as a Sr source or a Ba source and a compound serving as a Ga source at 300° C. or higher in an atmosphere containing 50 vol. % or more of water vapor to obtain an oxyhydroxide: A2Ga3O x (OZ) y (1) (In the general formula (1), A is Sr or Ba, Z is H or D, x is (6.5-0.5y), and y is 0.7 or more and 1.3 or less.)

[0018] (8) The present invention also relates to a method for producing an acid hydroxide represented by the following general formula (1), comprising: a precursor oxide preparation step of calcining a mixture containing a compound serving as a Sr source or a Ba source and a compound serving as a Ga source to obtain a precursor oxide; and an acid hydroxide conversion step of heating the precursor oxide obtained in the precursor oxide preparation step at 300° C. or higher in an atmosphere containing 50 vol. % or more of water vapor to obtain an acid hydroxide. A2Ga3O x (OZ) y (1) (In the general formula (1), A is Sr or Ba, Z is H or D, x is (6.5-0.5y), and y is 0.7 or more and 1.3 or less.)

[0019] (9) The present invention also relates to the method for producing an oxyhydroxide according to item (8), characterized in that the mixture is a gel obtained by mixing a compound serving as a Sr source or a Ba source, a compound serving as a Ga source, and a chelate compound.

[0020] (10) The present invention also relates to the method for producing an oxyhydroxide according to any one of (7) to (9), further comprising an annealing step of heat-treating the oxyhydroxide that has been subjected to the oxyhydroxide-forming step under an inert gas atmosphere.

[0021] (11) The present invention also relates to the method for producing an oxyhydroxide according to any one of items (7) to (9), wherein the compound serving as the Sr source is strontium nitrate, the compound serving as the Ba source is barium carbonate, and the compound serving as the Ga source is gallium nitrate, gallium sulfate, or gallium oxide.

[0022] (12) The present invention also relates to a method for producing an oxyhydroxide according to any one of (7) to (9), characterized in that the oxyhydroxide is represented by the chemical formula Sr2Ga3O6(OH), Sr2Ga3O6(OD), Ba2Ga3O6(OH) or Ba2Ga3O6(OD).

[0023] (13) The present invention also relates to a method for producing a fluorescent material, characterized in that the oxyhydroxide obtained by the method according to (10) is used as a fluorescent material. Effect of the Invention

[0024] According to the present invention, there are provided a new oxyhydroxide capable of suppressing water desorption even at higher temperatures, and a new rare metal-free phosphor. [Brief description of the drawings]

[0025] [Figure 1] FIG. 1 is a combination of a thermogravimetric analysis (TG) chart of the Sr-Ga oxyhydroxide obtained in Example 1 and mass spectrometry (Q-MS) data of the gas generated during heating, in which the upper row shows the TG chart, and the lower row shows the signal intensities representing m / z=18, 32, and 44 when the gas generated during heating was subjected to mass spectrometry. [Diagram 2] FIG. 2 is a combination of a thermogravimetric analysis (TG) chart of the Ba-Ga oxyhydroxide obtained in Example 2 and mass spectrometry (Q-MS) data of the gas generated during heating, in which the upper row shows the TG chart, and the lower row shows the signal intensities of m / z=17, 18, 32, and 44 when the gas generated during heating was subjected to mass spectrometry. [Diagram 3] FIG. 3 is a diffraction pattern obtained by X-ray diffraction measurement (CuKα) of the Sr—Ga oxyhydroxide obtained in Example 1. [Figure 4] FIG. 4 is a diffraction pattern obtained by X-ray diffraction measurement (CuKα) of the Ba—Ga oxyhydroxide obtained in Example 2. [Diagram 5] FIG. 5 shows the results of elemental analysis of the Sr-Ga oxyhydroxide obtained in Example 1 by energy dispersive X-ray spectroscopy (EDS). From the left in the upper row, a spectroscopic image showing the presence of Sr atoms, Ga atoms, and oxygen atoms in the crystal is shown, and the lower row is a SEM (scanning electron microscope) image of the same spot. [Figure 6] FIG. 6 shows the results of elemental analysis of the Ba-Ga oxyhydroxide obtained in Example 2 by energy dispersive X-ray spectroscopy (EDS). From the left in the upper row, a spectroscopic image showing the presence of Ga atoms, Ba atoms, and oxygen atoms in the crystal is shown, and the lower row is a SEM (scanning electron microscope) image of the same spot. [Figure 7] FIG. 7 is a fluorescence spectrum chart of the Sr—Ga oxyhydroxide obtained in Example 1 and the Ba—Ga oxyhydroxide obtained in Example 2, when the fluorescence spectrum was measured in a powder state using an excitation light with a wavelength of 254 nm. [Figure 8] FIG. 8 is a schematic diagram showing a part of the crystal structure of the oxyhydroxide of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] Hereinafter, an embodiment of the oxyhydroxide of the present invention, an embodiment of a fluorescent material, a first embodiment and a second embodiment of a method for producing the oxyhydroxide, and an embodiment of a method for producing a fluorescent material will be described. Note that the present invention is not limited to the following embodiment and embodiment.

[0027] <Oxid hydroxide> First, one embodiment of the oxyhydroxide of the present invention will be described. The oxyhydroxide of the present invention is a compound having a hexagonal crystal structure and represented by the following general formula (1). An oxyhydroxide is a compound having oxide ions and hydroxide ions in a crystal, and is expected to be used as, for example, a catalyst carrier or a catalyst due to the unique chemical environment based on the presence of these ions. However, in these applications, the oxyhydroxide is often exposed to high temperatures, and in such an environment, it is converted into an oxide by desorbing water (H2O) and losing hydroxide ions. In fact, as an oxyhydroxide, for example, Ba-In oxyhydroxide described in Non-Patent Document 1 and Patent Document 1 is known, but as described above, the oxyhydroxide described in Non-Patent Document 1 desorbs water from about 300°C in a dry atmosphere and cannot maintain the crystal structure of an oxyhydroxide in the medium temperature range, and the oxyhydroxide described in Patent Document 1 does not desorb water up to a medium temperature range of over 600°C, but does desorb water at higher temperatures. However, according to the Sr-Ga oxyhydroxide and Ba-Ga oxyhydroxide of the present invention represented by the following general formula (1), even when placed in a high temperature range of about 600 to 750°C, desorption of water is suppressed and the crystal structure of the oxyhydroxide is maintained. Thus, the oxyhydroxide of the present invention can be said to be a compound having higher thermal stability than conventionally known oxyhydroxides. In this specification, the compound in which A in the following general formula (1) is Sr is referred to as "Sr-Ga oxyhydroxide", and the compound in which A in the following general formula (1) is Ba is referred to as "Ba-Ga oxyhydroxide".

[0028] A2Ga3O x (OZ) y (1)

[0029] In the above general formula (1), A is Sr or Ba, Z is H or D, x is (6.5-0.5y), and y is 0.7 or more and 1.3 or less. In general formula (1), there is a charge of +13 due to divalent Sr or Ba ions and trivalent Ga ions, which is countered by monovalent hydroxide ions and divalent oxide ions, so if the number of hydroxide ions is y, the number of oxide ions x is (6.5-0.5y). If y is in the range of 0.7 to 1.3, the oxyhydroxide exhibits good heat resistance. The value of y is preferably in the range of 0.8 to 1.2, more preferably in the range of 0.9 to 1.1, and most preferably 1. When y is 1, the oxyhydroxide of the present invention is represented by the chemical formula Sr2Ga3O6(OH), Sr2Ga3O6(OD), Ba2Ga3O6(OH) or Ba2Ga3O6(OD). As is well known, D means a deuterium atom. In the following description, for the sake of simplicity, unless otherwise necessary, no distinction is made between hydrogen atoms and deuterium atoms, and they are collectively referred to as hydrogen atoms or H. For example, in the following paragraph, the term "OH site" means "OH or OD site."

[0030] The oxyhydroxide of the present invention may contain impurity elements in a total amount of 5 mol % or less based on the total number of ions at each of the Sr or Ba sites, the Ga sites, the O sites, and the OH sites.

[0031] As described above, the oxyhydroxide of the present invention includes Sr-Ga oxyhydroxide and Ba-Ga oxyhydroxide. These may each be a single oxyhydroxide or a solid solution in any ratio.

[0032] As data showing the heat resistance of the oxyhydroxide of the present invention, a combination of a thermogravimetric analysis (TG; heating rate 10° C. / min) chart of the Sr-Ga oxyhydroxide of the present invention obtained in Example 1 described later in a nitrogen atmosphere and mass spectrometry (Q-MS) data of the gas generated during heating is shown in FIG. 1. Also, a combination of a thermogravimetric analysis (TG; heating rate 10° C. / min) chart of the Ba-Ga oxyhydroxide of the present invention obtained in Example 2 described later in a nitrogen atmosphere and mass spectrometry (Q-MS) data of the gas generated during heating is shown in FIG. 2. FIG. 1 is a combination of a thermogravimetric analysis (TG) chart of the Sr-Ga oxyhydroxide obtained in Example 1 and mass spectrometry (Q-MS) data of the gas generated during heating, with the upper chart showing the TG chart and the lower chart showing the signal intensities of m / z=18, 32, and 44 when the gas generated during heating was subjected to mass spectrometry. FIG. 2 is a combination of a thermogravimetric analysis (TG) chart of the Ba-Ga oxyhydroxide obtained in Example 2 and mass spectrometry (Q-MS) data of the gas generated during heating, in which the upper row shows the TG chart, and the lower row shows the signal intensities representing m / z=17, 18, 32, and 44 when the gas generated during heating was subjected to mass spectrometry.

[0033] As shown in Fig. 1 and Fig. 2, the oxyhydroxide of the present invention shows two stages of mass reduction in the TG measurement, a gradual mass reduction of less than 1 mass% in the range of 100 to 300°C, and a large mass reduction of about 2.2 mass% (Sr-Ga oxyhydroxide in Fig. 1) or about 1.5 mass% (Ba-Ga oxyhydroxide in Fig. 2) in the range of about 630°C to about 900°C. In the latter large mass reduction, a signal representing m / z = 18 corresponding to the molecular weight of water is strongly observed, and it is found that the oxyhydroxide of the present invention causes desorption of water in the range of about 630°C to about 900°C, and the desorption is concentrated particularly at 850°C or higher (Sr-Ga oxyhydroxide) or 800°C or higher (Ba-Ga oxyhydroxide). That is, it can be understood that the oxyhydroxide of the present invention has thermal stability up to a high temperature range of about 600 to 800°C. The gradual mass decrease in the range of 100 to 300 °C also indicates the desorption of water (m / z = 18). However, this mass decrease stops once above 300 °C and shows a flat TG, so it is inferred to be due to the desorption of adsorbed water.

[0034] As described above, in thermogravimetric analysis in nitrogen, when the oxyhydroxide of the present invention is heated from 25°C to 900°C at a heating rate of 10°C / min, the mass loss due to water desorption at 600°C or higher and 900°C or lower is 1% by mass or more relative to the mass before heating, and the mass loss when heated from 25°C to 600°C is less than 1% by mass relative to the mass before heating, which indicates that the oxyhydroxide has high thermal stability.

[0035] Next, the diffraction pattern obtained by X-ray diffraction measurement of the Sr-Ga oxyhydroxide of the present invention obtained in Example 1 described later using CuKα radiation as an X-ray source is shown in FIG. 3. As shown in FIG. 3, the Sr-Ga oxyhydroxide has a crystal structure in which diffraction peaks appear in the ranges of 2θ=9.60° to 9.78°, 13.26° to 13.46°, 19.04° to 19.34°, 27.22° to 27.96°, 29.20° to 29.58°, and 31.50° to 32.22°. These are characteristic components based on the hexagonal crystal structure of the oxyhydroxide of the present invention, and in FIG. 3, these peaks are marked with downward arrows. Note that "the diffraction peak appears in the range of 2θ=X to Y°" means that the peak top of the peak is included in the range of X to Y. Therefore, for example, in a broad peak, it is not necessary that the peak is included from end to end.

[0036] FIG. 4 shows a diffraction pattern obtained by X-ray diffraction measurement of the Ba-Ga oxyhydroxide of the present invention obtained in Example 2 described later using CuKα radiation as an X-ray source. As shown in FIG. 4, the Ba-Ga oxyhydroxide has a crystal structure in which diffraction peaks appear in the ranges of 2θ=9.36°-9.57°, 12.82°-13.21°, 18.29°-19.10°, 25.89°-27.53°, 27.61°-29.48°, and 29.90°-32.11°. These are also characteristic components based on a hexagonal crystal structure, as in FIG. 3 showing Sr-Ga oxyhydroxide, and in FIG. 4, these peaks are marked with downward arrows.

[0037] As described above, Sr-Ga oxyhydroxide and Ba-Ga oxyhydroxide have characteristic peaks based on the hexagonal crystal structure in common, but due to differences in lattice constants, etc., Sr-Ga oxyhydroxide has a peak on the high angle side, while Ba-Ga oxyhydroxide has a peak on the low angle side. The oxyhydroxide of the present invention may be a solid solution of Sr-Ga oxyhydroxide and Ba-Ga oxyhydroxide. Taking these into consideration, it can be said that the oxyhydroxide of the present invention has a crystal structure in which diffraction peaks appear in the ranges of 2θ=9.36° to 9.80°, 12.82° to 13.56°, 18.29° to 19.61°, 25.89° to 28.37°, 27.61° to 30.39°, and 29.90° to 33.22°.

[0038] FIG. 5 shows the result of elemental analysis of the Sr-Ga oxyhydroxide of the present invention obtained in Example 1, which will be described later, by energy dispersive X-ray spectroscopy (EDS). FIG. 5 shows the result of elemental analysis of the Sr-Ga oxyhydroxide obtained in Example 1, by energy dispersive X-ray spectroscopy (EDS). The upper row shows, from the left to the right, a spectroscopic image showing the presence of Sr atoms, Ga atoms, and oxygen atoms in the crystal, and the lower row shows a SEM (scanning electron microscope) image of the same location. As shown in FIG. 5, each atom is uniformly present in the crystal, and it can be seen that this crystal is a single compound. In addition, the abundance ratio of the atoms calculated from the fluorescent X-ray intensity based on each atom was 12.78 at% for Sr, 19.20 at% for Ga, and 68.03 at% for O. This shows that the Sr / Ga ratio is about 0.67. The same result was obtained for the Ba-Ga oxyhydroxide obtained in Example 2, which will be described later, as shown in FIG. 6. FIG. 6 shows the results of elemental analysis of the Ba-Ga oxyhydroxide obtained in Example 2 by energy dispersive X-ray spectroscopy (EDS). From the left in the upper row, a spectroscopic image showing the presence of Ga atoms, Ba atoms, and oxygen atoms in the crystal is shown, and from the left in the lower row, a SEM image of the same portion is shown.

[0039] A schematic diagram showing a part of the crystal structure of the oxyhydroxide of the present invention is shown in Figure 8. As shown in this schematic diagram, it is understood that the hydroxyl groups are localized in the oxyhydroxide of the present invention. It is presumed that such localization leads to stabilization of the hydroxyl groups by hydrogen bonding, and therefore the oxyhydroxide of the present invention exhibits the high thermal stability described above.

[0040] As described above, the oxyhydroxide of the present invention has high thermal stability and can stably maintain its crystal structure up to about 800° C. (Ba-Ga oxyhydroxide) or 850° C. (Sr-Ga oxyhydroxide). Therefore, it can be used as a catalyst, catalyst carrier, proton conductor, electrode catalyst, etc. for use not only in the low to medium temperature range (up to 600° C.) but also in the high temperature range (600 to 800° C.). In addition, the oxyhydroxide of the present invention can also be used as a fluorescent emitter, which will be described later.

[0041] <First embodiment of the method for producing an oxyhydroxide> Next, a first embodiment of the method for producing an oxyhydroxide of the present invention will be described. Note that this embodiment and a second embodiment described later are both methods for producing an oxyhydroxide of the present invention.

[0042] The manufacturing method of this embodiment is characterized by including an acid hydroxide formation step in which a mixture containing a compound serving as a Sr source or Ba source and a compound serving as a Ga source is heated at 300°C or higher in an atmosphere containing 50% by volume or more of water vapor to obtain an acid hydroxide, and gives an acid hydroxide represented by the following general formula (1).

[0043] A2Ga3O x (OZ) y (1)

[0044] In the above general formula (1), A is Sr or Ba, Z is H or D, x is (6.5-0.5y), and y is 0.7 or more and 1.3 or less. This is as described above in the description of the oxyhydroxide of the present invention. The value of y is preferably in the range of 0.8 to 1.2, more preferably in the range of 0.9 to 1.1, and most preferably 1. When y is 1, the oxyhydroxide of the present invention is represented by the chemical formula Sr2Ga3O6(OH), Sr2Ga3O6(OD), Ba2Ga3O6(OH), or Ba2Ga3O6(OD). This is also as described above in the description of the oxyhydroxide of the present invention.

[0045] The compound serving as a Sr source means a compound that supplies Sr when synthesizing the oxyhydroxide of the present invention. The compound serving as a Sr source is not particularly limited as long as it contains Sr. Preferred examples of such compounds include Sr salts such as strontium nitrate, strontium carbonate, strontium sulfate, strontium chloride, strontium acetate, and strontium hydroxide, and Sr peroxides such as strontium peroxide, and among these, strontium nitrate is more preferred.

[0046] The compound serving as a Ba source means a compound that supplies Ba when synthesizing the oxyhydroxide of the present invention. The compound serving as a Ba source is not particularly limited as long as it contains Ba. Preferred examples of such compounds include Ba salts such as barium nitrate, barium carbonate, barium sulfate, barium chloride, barium acetate, barium hydroxide, etc., and Ba peroxides such as barium peroxide, and among these, barium carbonate is more preferred.

[0047] The compound serving as a Ga source means a compound that supplies Ga when synthesizing the oxyhydroxide of the present invention. Such a compound serving as a Ga source may be any compound containing Ga, but is preferably a salt or oxide containing Ga. Preferred examples of the salt or oxide containing Ga include gallium nitrate, gallium carbonate, gallium sulfate, gallium chloride, gallium acetate, gallium hydroxide, and gallium oxide, and among these, gallium nitrate, gallium sulfate, and gallium oxide are more preferred. Gallium nitrate is commercially available in the form of an "n-hydrate", and such a commercially available product may be obtained and used. Preferred examples of n in the "n-hydrate" include about 6 to 8.

[0048] The compound serving as the Sr source or Ba source and the compound serving as the Ga source are mixed together to form a mixture prior to carrying out the oxyhydroxidation process. The means for preparing the mixture is not particularly limited, but includes a method of mixing them using a mortar. When mixing, an appropriate amount of alcohol may be added and wet-pulverized. The mixture thus obtained is preferably compressed into pellets, but is not particularly limited thereto. The mixing ratio of the two is preferably 2:3 molar ratio of the compound serving as the Sr source or Ba source: the compound serving as the Ga source. The mixture thus obtained is subjected to the oxyhydroxidation process.

[0049] [Acid hydroxide process] The acid hydroxide forming step is a step of carrying out an acid hydroxide forming reaction by heating the mixture at 300° C. or higher in an atmosphere containing 50% by volume or more of water vapor. By carrying out this reaction, the mixture is converted into the acid hydroxide of the present invention having a hexagonal crystal structure.

[0050] The heating temperature may be 300° C. or higher, preferably 400° C. or higher, more preferably 450° C. or higher, and even more preferably 500° C. or higher. On the other hand, the heating temperature is preferably 750° C. or lower, more preferably 700° C. or lower, and even more preferably 650° C. or lower. By setting the heat treatment temperature to the above value or lower, it is possible to suppress desorption of water from the hexagonal crystal structure of the oxyhydroxide once formed.

[0051] The atmosphere in the oxyhydroxidization reaction is not particularly limited as long as it contains 50% or more of water vapor by volume, but the amount of water vapor in the atmosphere is preferably 65% ​​or more by volume, more preferably 75% or more by volume, and even more preferably 80% or more by volume. On the other hand, the amount of water vapor in the atmosphere can be 100% or less by volume or 90% or less by volume. In addition, as the atmospheric gas other than water vapor, it is preferable to use a gas that does not react with the compound serving as the Sr source or Ba source, the compound serving as the Ga source, and water vapor. Examples of such a gas include nitrogen and argon, which are generally known as inert gases. In addition, when water vapor from water (H2O) is used in the oxyhydroxidization reaction, an oxyhydroxide in which Z is H in the above general formula (1) is obtained, and when water vapor from heavy water (D2O) is used, an oxyhydroxide in which Z is D in the above general formula (1) is obtained.

[0052] The heating time is preferably 30 minutes or more, more preferably 1 hour or more, further preferably 1.5 hours or more, and particularly preferably 3 hours or more. When a mixture of a Ba source and a Ga source is used for oxyhydroxidization, it often takes a longer time than when a mixture of a Sr source and a Ga source is used, and a heating time of about 10 hours or more is preferable.

[0053] The oxyhydroxide obtained through the oxyhydroxide-forming step can be used as it is, but is preferably subjected to the annealing step described below.

[0054] [Annealing process] The annealing step is a step in which the oxyhydroxide that has been subjected to the oxyhydroxide conversion step is heat-treated under an inert gas atmosphere to remove impurities contained in the oxyhydroxide. This step increases the purity of the oxyhydroxide. The oxyhydroxide of the present invention can be used as a fluorescent material as described below, and when used for this purpose, it is essential to pass through the annealing step.

[0055] Examples of the inert gas used in the annealing step include nitrogen and argon. The heat treatment temperature in the case of Sr-Ga oxyhydroxide is preferably 500°C or higher, more preferably 550°C or higher. The temperature is preferably 750°C or lower, more preferably 700°C or lower, and even more preferably 650°C or lower. The heat treatment temperature in the case of Ba-Ga oxyhydroxide is preferably about 500°C. By setting the heat treatment temperature in this range, impurities can be removed well and desorption of water from the oxyhydroxide accompanying the heat treatment can be suppressed, which is preferable.

[0056] <Second embodiment of the method for producing an oxyhydroxide> Next, a second embodiment of the method for producing an oxyhydroxide of the present invention will be described. In the method for producing the first embodiment described above, a mixture of a compound serving as a Sr source or a Ba source and a compound serving as a Ga source is directly subjected to the oxyhydroxidization step, but in the method for producing the present embodiment (second embodiment), a mixture of a compound serving as a Sr source or a Ba source and a compound serving as a Ga source is fired to form a precursor oxide containing Sr and Ga or a precursor oxide containing Ba and Ga, and then the fired product is subjected to the oxyhydroxidization step.

[0057] The manufacturing method of this embodiment is characterized by including a precursor oxide preparation step of calcining a mixture containing a compound serving as a Sr source or Ba source and a compound serving as a Ga source to obtain a precursor oxide, and an acid hydroxide conversion step of heating the precursor oxide obtained in this step at 300°C or higher in an atmosphere containing 50% or more by volume of water vapor to obtain an acid hydroxide represented by the following general formula (1).

[0058] A2Ga3O x (OZ) y (1)

[0059] In the above general formula (1), x, A is Sr or Ba, Z is H or D, (6.5-0.5y), and y is 0.7 or more and 1.3 or less. This is as described in the description of the oxyhydroxide of the present invention. The value of y is preferably in the range of 0.8 to 1.2, more preferably in the range of 0.9 to 1.1, and most preferably 1. When y is 1, the oxyhydroxide of the present invention is represented by the chemical formula Sr2Ga3O6(OH), Sr2Ga3O6(OD), Ba2Ga3O6(OH), or Ba2Ga3O6(OD). This is also as described in the description of the oxyhydroxide of the present invention. Each step will be described below.

[0060] [Precursor oxide preparation process] First, the precursor oxide preparation step will be described. This step is a step of firing a mixture containing a compound serving as a Sr source or a Ba source and a compound serving as a Ga source to obtain a precursor oxide containing Sr and Ga or a precursor oxide containing Ba and Ga. Note that the compound serving as the Sr source, the compound serving as the Ba source, and the compound serving as the Ga source are the same as those described in the first embodiment, so the description here will be omitted.

[0061] When the compound serving as the Ga source and the compound serving as the Sr source or Ba source are mixed to form a mixture, the two solid compounds may be mixed evenly in a mortar or the like to form a mixture by dry grinding, or alcohol may be added thereto to form a wet grinding, as in the first embodiment, or solutions of the two compounds may be mixed and then gelled with a chelating agent to form a mixture by wet mixing. In any case, it is preferable to mix the compound serving as the Sr source or Ba source:the compound serving as the Ga source in a molar ratio of 2:3.

[0062] When wet mixing is performed, for example, strontium nitrate or barium carbonate and gallium nitrate n-hydrate are weighed so that the molar ratio of Sr:Ga or Ba:Ga is 2:3, dissolved in pure water or lactic acid solution, and a solution of citric acid is added to the solution in an amount of about three times the total molar amount of metal contained in the solution and stirred. Here, citric acid acts as a chelating agent for metals, and the above stirring causes the solution to gel. The gel thus obtained can be fired as it is. When wet mixing is performed, by preparing a mixture using a chelating agent in this way, it is possible to suppress changes in the component ratio due to segregation. In addition, by using an organic substance as a chelating agent, it is decomposed and removed during the subsequent firing. In addition, the n in the above-mentioned "n-hydrate" can preferably be about 6 to 8.

[0063] The mixture obtained by dry grinding, wet grinding, or wet mixing is converted into a precursor oxide containing triclinic Sr3Ga4O9 or hexagonal BaGa2O4 by firing. When performing this firing, it is preferable to perform the firing after performing multiple calcinations. Examples of such calcinations and firings include performing the first calcination in the air at 450°C for 1 hour, then performing the second calcination in the air at 600°C for 1 hour, then performing the third calcination in the air at 1000°C for 10 hours, and finally performing the calcination in the air at 1200°C for 10 hours, but are not particularly limited thereto. In addition, it is preferable to compress the obtained precursor oxide into a pellet shape before performing the oxyhydroxidization process described later.

[0064] The precursor oxide prepared by calcination is subjected to an oxyhydroxidization step.

[0065] [Acid hydroxide process] The acid hydroxide forming step is a step of obtaining an acid hydroxide by heating the precursor oxide obtained in the precursor oxide preparing step at 300° C. or higher in an atmosphere containing 50% by volume or more of water vapor. By carrying out this reaction, the precursor oxide is converted into the acid hydroxide of the present invention having a hexagonal crystal structure.

[0066] The heating temperature may be 300° C. or higher, preferably 400° C. or higher, more preferably 450° C. or higher, and even more preferably 500° C. or higher. On the other hand, the heating temperature is preferably 750° C. or lower, more preferably 700° C. or lower, and even more preferably 650° C. or lower. By setting the heat treatment temperature to the above value or lower, it is possible to suppress desorption of water from the hexagonal crystal structure of the oxyhydroxide once formed.

[0067] The atmosphere in the oxyhydroxidization reaction is not particularly limited as long as it contains 50% or more of water vapor by volume, but the amount of water vapor in the atmosphere is preferably 65% ​​or more by volume, more preferably 75% or more by volume, and even more preferably 80% or more by volume. On the other hand, the amount of water vapor in the atmosphere can be 100% or less by volume or 90% or less by volume. In addition, as the atmospheric gas other than water vapor, it is preferable to use a gas that does not react with the compound serving as the Sr source or Ba source, the compound serving as the Ga source, and water vapor. Examples of such a gas include nitrogen and argon, which are generally known as inert gases. In addition, when water vapor from water (H2O) is used in the oxyhydroxidization reaction, an oxyhydroxide in which Z is H in the above general formula (1) is obtained, and when water vapor from heavy water (D2O) is used, an oxyhydroxide in which Z is D in the above general formula (1) is obtained.

[0068] The heating time is preferably 30 minutes or more, more preferably 1 hour or more, further preferably 1.5 hours or more, and particularly preferably 3 hours or more.

[0069] The oxyhydroxide obtained through the oxyhydroxide-forming step can be used as it is, but is preferably subjected to the annealing step described below.

[0070] [Annealing process] The annealing step is a step of removing impurities contained in the oxyhydroxide by heat-treating the oxyhydroxide that has been subjected to the oxyhydroxidization step under an inert gas atmosphere. This step increases the purity of the oxyhydroxide. The oxyhydroxide of the present invention can be used as a fluorescent emitter as described below, but when used for this purpose, it is essential to pass through the annealing step. The annealing step in the second embodiment is the same as the annealing step in the first embodiment, and therefore will not be described here.

[0071] <Fluorescent emitter> The above-mentioned fluorescent material made of the oxyhydroxide of the present invention is also one of the present inventions. The oxyhydroxide of the present invention, regardless of whether A in the above general formula (1) is Sr or Ba, emits strong yellow fluorescent light when irradiated with short-wavelength ultraviolet light, such as 254 nm. As can be seen from the fact that it emits light when irradiated with short-wavelength ultraviolet light, the oxyhydroxide of the present invention has a significantly low absorption efficiency in the visible light region. Therefore, the oxyhydroxide of the present invention, which is a completely white powder before being irradiated with short-wavelength ultraviolet light, only exhibits a yellow color when irradiated with short-wavelength ultraviolet light. This is in contrast to many fluorescent materials, which have slight absorption in the visible light region and can be observed to have a color tone corresponding to the fluorescent color even before light irradiation.

[0072] It is not entirely clear why the oxyhydroxide of the present invention exhibits such strong fluorescent emission. However, since Sr2Ga3O6F, which is not an oxyhydroxide, does not exhibit the same luminescence as Sr2Ga3O6(OH), which is an oxyhydroxide, it is possible that the OH in the crystal structure of the oxyhydroxide - This suggests that the oxyhydroxide of the present invention may contribute to the emission of light. Interestingly, the oxyhydroxide of the present invention exhibits stronger fluorescence when Z is D (deuterium atom) than when Z is H in the above general formula (1). As already mentioned, such a deuterated oxyhydroxide can be obtained by using steam of heavy water (DO) instead of steam of water (HO) in the oxyhydroxide formation step in the above production method of the present invention.

[0073] <Method of manufacturing fluorescent material> The above-mentioned method for producing a fluorescent material is also one aspect of the present invention. This method is characterized in that the oxyhydroxide obtained by the above-mentioned method for producing an oxyhydroxide of the present invention is used as a fluorescent material. These matters have already been described, so description thereof will be omitted here. EXAMPLES

[0074] The present invention will be described in more detail below by showing examples, but the present invention is not limited to the following examples in any way.

[0075] [Example 1] A mixture of strontium nitrate (20 mmol) in ultrapure water (60 mL), gallium nitrate n-hydrate (30 mmol) in ultrapure water (90 mL), and citric acid (50 mmol) in ultrapure water (150 mL) was added to a beaker and stirred to prepare a mixed solution. This mixed solution was left overnight at 120 °C to gel. The gel obtained was calcined in air at 450 °C for 1 hour using a mantle heater, and then calcined in air at 600 °C for 1 hour using a box furnace to remove all residual organic matter. The calcined powder was then calcined in air at 1000 °C for 10 hours, and then calcined in air at 1200 °C for 10 hours to obtain a precursor oxide. Next, 0.6 g of the obtained precursor oxide was added to a mortar together with methanol (5 mL) and mixed. After the methanol evaporated, the mixture was molded into pellets using a molding die at a uniaxial pressure of about 5 MPa. Thereafter, the obtained molded body was reacted in 80% by volume water vapor at 500°C for 3 hours, and further heat-treated at 600°C for 3 hours in a nitrogen atmosphere to obtain Sr-Ga oxyhydroxide.

[0076] The obtained Sr-Ga oxyhydroxide was subjected to X-ray diffraction measurement using CuKα radiation as an X-ray source. The results are shown in Figure 3. As shown in Figure 3, the Sr-Ga oxyhydroxide has a crystal structure in which diffraction peaks appear in the ranges of 2θ = 9.60° to 9.78°, 13.26° to 13.46°, 19.04° to 19.34°, 27.22° to 27.96°, 29.20° to 29.58°, and 31.50° to 32.22°. These peaks are characteristic components based on the hexagonal crystal structure of the oxyhydroxide of the present invention.

[0077] The obtained Sr-Ga oxyhydroxide was subjected to elemental analysis by energy dispersive X-ray spectroscopy (EDS). The results are shown in FIG. 5. As already mentioned, FIG. 5 shows the results of elemental analysis of Sr-Ga oxyhydroxide by EDS, in which the upper row shows, from the left to the right, a spectroscopic image showing the presence of Sr atoms, Ga atoms, and oxygen atoms in the crystal, and the lower row shows a SEM (scanning electron microscope) image of the same location. As shown in FIG. 5, each atom is uniformly present in the crystal, and it can be seen that this crystal is almost a single compound. In addition, the atomic ratios calculated from the fluorescent X-ray intensity based on each atom were 12.78 at% Sr, 19.20 at% Ga, and 68.03 at% O. This shows that the Sr / Ga ratio is about 0.67.

[0078] Next, the thermal stability of the obtained Sr-Ga oxyhydroxide was evaluated. In this evaluation, the obtained oxyhydroxide was subjected to thermogravimetric analysis (TG) and mass analysis of the gas generated during heating using a thermogravimetric analyzer and a mass analyzer (Q-MS). The results are shown in FIG. 1. As already mentioned, FIG. 1 is a combination of the thermogravimetric analysis (TG) chart of the Sr-Ga oxyhydroxide obtained in Example 1 and the mass analysis (Q-MS) data of the gas generated during heating, in which the upper part shows the TG chart and the lower part shows the signal intensities of m / z=18, 32, and 44 when the gas generated during heating was subjected to mass analysis.

[0079] 1, the Sr-Ga oxyhydroxide showed two stages of mass loss in the TG measurement, a gradual mass loss of less than 1 mass% in the range of 100 to 300°C, and a large mass loss of about 2.2 mass% in the range of about 630 to 900°C. In the latter large mass loss, a signal representing m / z=18 corresponding to the molecular weight of water was strongly observed, and it was found that the obtained Sr-Ga oxyhydroxide caused desorption of water in the range of about 630 to 900°C, and the desorption was particularly concentrated at 850°C or higher. That is, it can be understood that the Sr-Ga oxyhydroxide of Example 1 has good thermal stability because water desorption is suppressed up to a high temperature range of about 600 to 800°C.

[0080] [Example 2] Ethanol (5 mL) was added as a grinding aid to barium carbonate (10 mmol) and gallium oxide (15 mmol), and the mixture was wet-ground using a mortar. The mixture was calcined at 1000°C in air for 10 hours, and the calcined powder was then fired at 1200°C in air for 10 hours to obtain a precursor oxide. The precursor oxide was then molded into pellets using a molding die at a uniaxial pressure of about 5 MPa. The molded product was then reacted at 500°C in 80% by volume water vapor for 12 hours, and further heat-treated at 500°C in a nitrogen atmosphere for 3 hours to obtain Ba-Ga oxyhydroxide.

[0081] The obtained Ba-Ga oxyhydroxide was subjected to X-ray diffraction measurement using CuKα radiation as an X-ray source. The results are shown in Figure 4. As shown in Figure 4, Ba-Ga oxyhydroxide has a crystal structure in which diffraction peaks appear in the ranges of 2θ = 9.36° to 9.57°, 12.82° to 13.21°, 18.29° to 19.10°, 25.89° to 27.53°, 27.61° to 29.48°, and 29.90° to 32.11°. These peaks are characteristic components based on the hexagonal crystal structure of the oxyhydroxide of the present invention.

[0082] The obtained Ba-Ga oxyhydroxide was subjected to elemental analysis by energy dispersive X-ray spectroscopy (EDS). The results are shown in FIG. 6. As already mentioned, FIG. 6 shows the results of elemental analysis by EDS of the oxyhydroxide of the present invention, in which, from the left in the upper row, are spectroscopic images showing the presence of Ga atoms, Ba atoms, and oxygen atoms in the crystal, and the lower row is an SEM image of the same location. As shown in FIG. 6, each atom is uniformly present in the crystal, and it can be seen that this crystal is almost a single compound, similar to the previous Sr-Ga oxyhydroxide.

[0083] Next, the thermal stability of the obtained Ba-Ga oxyhydroxide was evaluated. In this evaluation, similarly to the evaluation of the Sr-Ga oxyhydroxide, the obtained oxyhydroxide was subjected to thermogravimetric analysis (TG) and mass analysis of the gas generated during heating was performed using a thermogravimetric analyzer and a mass analyzer (Q-MS). The results are shown in FIG. 2. As already mentioned, FIG. 2 is a combination of a thermogravimetric analysis (TG) chart of the Ba-Ga oxyhydroxide obtained in the example and mass analysis (Q-MS) data of the gas generated during heating, in which the upper part shows the TG chart and the lower part shows the signal intensities of m / z=17, 18, 32, and 44 obtained by mass analysis of the gas generated during heating.

[0084] 2, the Ba-Ga oxyhydroxide shows two stages of mass loss in the TG measurement, a gradual mass loss of less than 0.1 mass% in the range of 100 to 300°C, and a large mass loss of about 1.5 mass% in the range of about 650 to 900°C. In the latter large mass loss, a signal representing m / z=18 corresponding to the molecular weight of water is strongly observed, and it is found that the obtained Ba-Ga oxyhydroxide causes desorption of water in the range of about 650 to 900°C, and the desorption is concentrated especially at 800°C or higher. That is, it can be understood that the Ba-Ga oxyhydroxide of Example 2 has good thermal stability because desorption of water is suppressed up to a high temperature range of about 600 to 800°C.

[0085] For each of the Sr-Ga oxyhydroxide obtained in Example 1 and the Ba-Ga oxyhydroxide obtained in Example 2, the fluorescence spectrum was measured in a powder state using an excitation light of 254 nm wavelength. The results are shown in FIG. 7. As shown in FIG. 7, broad fluorescence emission was observed at wavelengths of 450 to 600 nm for both the Sr-Ga oxyhydroxide and the Ba-Ga oxyhydroxide. It is surprising that such fluorescence emission is observed in inorganic compounds that do not contain rare earth elements. In FIG. 7, the peaks appearing near 510 nm and 760 nm are secondary and tertiary lights of the excitation light, respectively.

Claims

1. An oxyhydroxide having a hexagonal crystal structure and represented by the following general formula (1): A 2 Go 3 Oh x (OZ) y ・・・・(1) (In the general formula (1), A is Sr or Ba, Z is H or D, x is (6.5-0.5y), and y is 0.7 or more and 1.3 or less.)

2. The oxyhydroxide according to claim 1, wherein, in a thermogravimetric analysis in nitrogen, when the temperature is raised from 25°C to 900°C at a heating rate of 10°C / min, the mass loss due to water desorption at 600°C or higher and 900°C or lower is 1 mass% or more relative to the mass before heating.

3. 2. The oxyhydroxide according to claim 1, which, in a thermogravimetric analysis in nitrogen, loses less than 1% by mass when heated from 25°C to 600°C at a heating rate of 10°C / min relative to the mass before heating.

4. The diffraction peak in the diffraction pattern measured by X-ray diffraction measurement using CuKα radiation as an X-ray source is at least 2θ=9.36° to 9.80°, 12.82° to 13.56°, 18.29° to 19.61°, 25.89° to 28.37°, 27.61° to 30.39°, and 29.90° to 33.22° The oxyhydroxide according to claim 1, having a crystal structure which appears in each of the ranges.

5. Sr 2 G 3 O 6 (OH), Sr 2 G 3 O 6 (OD), Ba 2 G 3 O 6 (OH) or Ba 2 G 3 O 6 The acid hydroxide according to claim 1, characterized in that it is represented by the chemical formula: (OD).

6. A fluorescent material comprising the oxyhydroxide according to any one of claims 1 to 5.

7. A method for producing an acid hydroxide represented by the following general formula (1), comprising an acid hydroxide formation step of heating a mixture containing a compound serving as a Sr source or a Ba source and a compound serving as a Ga source at 300° C. or higher in an atmosphere containing 50 vol. % or more of water vapor to obtain an acid hydroxide. A 2 Go 3 Oh x (OZ) y ・・・・(1) (In the general formula (1), A is Sr or Ba, Z is H or D, x is (6.5-0.5y), and y is 0.7 or more and 1.3 or less.)

8. A method for producing an acid hydroxide represented by the following general formula (1), comprising: a precursor oxide preparation step of calcining a mixture containing a compound serving as a Sr source or a Ba source and a compound serving as a Ga source to obtain a precursor oxide; and an acid hydroxide conversion step of heating the precursor oxide obtained in this step at 300° C. or higher in an atmosphere containing 50 vol. % or more of water vapor to obtain an acid hydroxide. A 2 Go 3 Oh x (OZ) y ・・・・(1) (In the general formula (1), A is Sr or Ba, Z is H or D, x is (6.5-0.5y), and y is 0.7 or more and 1.3 or less.)

9. 9. The method for producing an oxyhydroxide according to claim 8, wherein the mixture is a gel obtained by mixing a compound serving as a Sr source or a Ba source, a compound serving as a Ga source, and a chelate compound.

10. The method for producing an oxyhydroxide according to any one of claims 7 to 9, further comprising an annealing step of heat-treating the oxyhydroxide that has been subjected to the oxyhydroxide-forming step in an inert gas atmosphere.

11. The method for producing an oxyhydroxide according to any one of claims 7 to 9, wherein the compound serving as the Sr source is strontium nitrate, the compound serving as the Ba source is barium carbonate, and the compound serving as the Ga source is gallium nitrate, gallium sulfate, or gallium oxide.

12. The oxyhydroxide is Sr 2 G 3 O 6 (OH), Sr 2 G 3 O 6 (OD), Ba 2 G 3 O 6 (OH) or Ba 2 G 3 O 6 The method for producing an oxyhydroxide according to any one of claims 7 to 9, characterized in that the oxyhydroxide is represented by the chemical formula (OD).

13. A method for producing a fluorescent material, comprising using an oxyhydroxide obtained by the method according to claim 10 as a fluorescent material.

Citation Information

Patent Citations

  • Ceramic composite, and fluophor for projector and light emitting device containing the same

    JP2019006967A

  • Acid hydroxide, method for producing the same, proton conductor, and catalyst carrier

    JP2020070203A